2012
DOI: 10.1111/j.1747-6593.2012.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of toxic cyanobacterial blooms for the first time in Lake Karaoun, Lebanon

Abstract: The increasing occurrence of cyanobacterial bloom in freshwaters worldwide is of great importance because of public health risks. In addition, they are very likely to have negative impact on ecological and economic aspects. In this study, the seasonal succession of phytoplankton population in Lake Karaoun in Lebanon was monitored from May 2009 to June 2011. The physicochemical parameters of lake water were then monitored for 1 year, from June 2010 until June 2011, to correlate the physicochemical parameters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Humphries and Lyne (1988) found that high rising velocities of Microcystis aeruginosa could concentrate them near the surface, and favour scum formation and thus losses from wind-driven advection to the edges. Visible scums at the edges of Karaoun Reservoir were previously reported by Atoui et al (2013).…”
Section: Model Performance For Cyanobacterial Biomassesmentioning
confidence: 99%
“…Humphries and Lyne (1988) found that high rising velocities of Microcystis aeruginosa could concentrate them near the surface, and favour scum formation and thus losses from wind-driven advection to the edges. Visible scums at the edges of Karaoun Reservoir were previously reported by Atoui et al (2013).…”
Section: Model Performance For Cyanobacterial Biomassesmentioning
confidence: 99%
“…et Flah. and Planktothrix agardhii (Gomont) Anagnostidis et Komárek (Teubner et al, 1999), Anabaena circinalis Rabenh or Cylindrospermopsis raciborskii (Woloszyńska) Seenayya et Subba Raju and Microcystis aeruginosa Kützing (Soares et al, 2009), Cylindrospermopsis raciborskii and Aphanizomenon ovalisporum Forti (Messineo et al, 2010), Aphanizomenon or Anabaena and Microcystis (Tsukada et al, 2006), and Microcystis aeruginosa and Aphanizomenon ovalisporum (Atoui et al, 2013). Many factors influence the competition and succession among different cyanobacterial genera, such as nitrogen, phosphorus, the ratio of total nitrogen to total phosphorus, water temperature, light intensity, thermal stratification, allelopathic effects, grazing, competition, etc., and they play a role in succession either individually or synergistically (Scheffer & Carpenter, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Understanding the physical processes that occur inside the reservoir and its driven forces is crucial for the management and optimization of these systems, especially those utilized for drinking water and power generation. The water circulation and mixing process can be related with phytoplankton dynamics (Vidal et al 2010), iron and manganese release (Tundisi et al 2004), phosphorus dynamics (Komatsu et al 2006), cyanobacteria bloom (Atoui et al 2012), and greenhouse gas emissions (Rudorff et al 2011).…”
Section: Introductionmentioning
confidence: 99%